2018
DOI: 10.1039/c8ra07320a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Zn3(VO4)2/BiVO4 heterojunction composite for the photocatalytic degradation of methylene blue organic dye and electrochemical detection of H2O2

Abstract: In this study, a Zn3(VO4)2/BiVO4 heterojunction nanocomposite photocatalyst was prepared using a hydrothermal route with different molar concentration ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…e EDX is a significant technique to determine the chemical composition [27]. EDX spectrum is shown in Figure 7, which reveals that the elements within synthesized NiO-ZnO NC are nickel, zinc, oxygen, and carbon.…”
Section: Edx Analysismentioning
confidence: 99%
“…e EDX is a significant technique to determine the chemical composition [27]. EDX spectrum is shown in Figure 7, which reveals that the elements within synthesized NiO-ZnO NC are nickel, zinc, oxygen, and carbon.…”
Section: Edx Analysismentioning
confidence: 99%
“…The intensity of this peak increases with the calcination temperature indicating a fast charge recombination of photo-generated charge carriers (electrons and holes) with suppression the photocatalytic activity. [31][32][33] From the PL spectra, the BiVO 4 NPs calcinated at 400 C is identied to support slower charge recombination, whose rate increases with the increasing calcination temperature towards 600 C. Due to this, the The decomposition percentage of photocatalyst has been calculated using Beer-Lambert's law given below.…”
Section: Photocatalytic Dye Degradation Studies Of Bivo 4 Npsmentioning
confidence: 99%
“…It is observed that the 1T-MoS 2 @(Bi 0.40 Fe 0.60 )VO 4 composite exhibits the lowest PL emission intensity, indicating a large separation efficiency of photogenerated charge carriers. 34 To further understand the charge transfer in 1T-MoS 2 @(Bi 1− x Fe x )VO 4 photocatalysts, the electrochemical impedance spectroscopy (EIS) technique was used. The measurement was also carried out for a bare glassy carbon electrode (GCE) and 1T-MoS 2 @(Bi 0.40 Fe 0.60 )VO 4 composite.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen cooling system containing an ice bath was used to keep the temperature constant and to avoid thermal degradation or decomposition throughout the experimentation. 34,35,57 The degradation efficiency of the dye (CV%) solutions was obtained by the following formula: 32,34 where C 0 is the initial concentration of dye solution and C is the concentration of dye after every interval of 10 minutes. 34 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation